Família, proteção social e trabalho social com a minha, a sua e a nossa família - Santos, Rosemeire dos (2016)
Family, Social Protection and Social Work, mine, yours and our family, is the product of understanding that social work with families can be a way of amplifying social protection when adopted by axes and strategies access to social security that extend the protective conditions of family and social rights of citizens to the family as a whole and its members with the recognition of citizenship, in the context of distributive social policies, or non-contributory, which comprises the Brazilian social Security. Thus, the discussion focuses on the understanding that social protection to families develops both in the private sphere, in which the statement is based on the understanding of the discussion of "Way (s) of Being Family", questioning that the social construction of the family, put it in charge of the protection, maintenance and survival of its members, regardless of their composition but by the conviviality and solidarity that they belong; however, social protection is not only limited in the private sector it is also in the public domain, as the state's responsibility to provide access to social security for families and individuals so that they can engage in private responsibilities, considerations of public liabilities is due to the development of the study in "Way (s) of social protection of the family , understanding that there are situations of family unprotected by not understanding the needs, as well the development of social security in the distributive social policies that enable the realization of social protection in public life as also collaborated on conducting effective or not in the same private sphere of the family. In this bias the mode (s) of Social Work with Families dedicated to comprehend the category "Work", reflecting the difference between social work with families and family support, from four experiences developed or under development, in which are three Latin American experiences and a European. Resulting in the defense that social work with families is much more than an accompanying conditionality s and rules adjustment, and that its direction, planning and execution must be for purposes of recognition of rights and citizenship, collaborating with the emancipation and social role of families and individuals involved